Effects Of Cu On The Modified Co-Based Catalyst Activity For Fischer-Tropsch Synthesis - Zaky Al Fatony; Ahlul Hafizan Resha; Galang Putra Persada; IGBN Makertihartha; Melia Laniwati Gunawan; Subagjo Subagjo (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
Future fuel scarcity issue has become major concern for many energy security policies. As a very potential process to produce fuel, Fischer-Tropsch synthesis (FTS) with cobalt-based catalyst has been developed to produce wax as feedstock for further catalytic cracking. Therefore, this research was conducted to observe Co/Al2O3 catalyst properties enhancement through support pre-treatment using NH4NO3 and Cu promoter addition toward higher activity and selectivity. Catalysts were prepared by dry impregnation method. XRD, BET and TPR analyses were performed to characterize catalysts properties. Activity tests showed CO conversion, H2 conversion and selectivity of C5+ were in the range of 25.1% to 96.2%, 24.2% to 83.7% and 53.5% to 75.9% respectively. Crystallography measurements exhibited 8.6-9.8 nm cobalt particles size. In this study, FTS was evaluated by using fixed-bed reactor at 20 bar, 250 C, and WHSV of 1500 ml/g.cat/h-1. Support pre-treatment increased the pore size of γ-Al2O3 and slightly enlarged cobalt diameter. While addition of Cu improved the reducibility of the catalyst.